Effect of Shear Strength of Oil on Lubrication of Cold Strip Rolling in Full-Fil Regime - Latifi, Seyedmorteza (Logic : Jurnal Rancang Bangun dan Teknologi, 2020)
Cold strip rolling is a major deformation process in industry. The need for high quality products and increased production speed, makes the application of the lubricant important. In the present study, oil property effect is investigated in cold rolling using oil lubricant in full-film lubrication regime. The model predicts decisive role of oil property in rolling parameters.